Organic Transistor Devices for In Vitro Electrophysiological Applications - Spanu, Andrea; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This thesis reports on the Micro OCMFET Array, a novel, reference-less system for extracellular recordings of action potentials. The book provides readers with a full description of the system, together with an extensive report of the successful experimental trials carried out on both cardiac and nerve cells. Moreover, it offers a concise yet comprehensive overview of both bioelectronic interfaces, such as Micro Electrode Arrays (MEAs) and Field Effect Devices (FEDs), and organic sensors for electro- physiological applications, including Organic Charge-Modulated FETs (OCMFET), Electrolyte-Gated Organic FETs (EGOFETs), and Organic Electrochemical Transistors (OECTs).
Introduction -- Bio-electronics Interfaces -- Organic Devices for Electrophysiological Applications -- The Micro Organic Charge Modulated FET Array -- Experimental Results.-Conclusions.
Keywords: Biomedical engineering; Cytology; Electronics; Neurosciences; Biomedical Engineering and Bioengineering; Cell Biology; Electronics and Microelectronics, Instrumentation; Neuroscience